Epidemiology and variables involved in dental abscess: survey of dental emergency unit in Trieste. (23rd July 2013) - Ottaviani, G; Costantinides, F; Perinetti, G; Luzzati, R; Contardo, L; Visintini, E; Tirelli, G; Di Lenarda, R; Gobbo, M; Biasotto, M
<x xml:space="preserve">Abstract</x> Objectives The objective of this epidemiologic study was to estimate the healing time of acute dental abscesses and to evaluate the main variables involved in the healing process itself. Subjects and Methods Among a sample of over 24 000 patients visited at the emergency dental unit, 688 subjects were diagnosed with dental abscess and enrolled in the study. Case histories of all patients were collected to investigate the clinical course and healing time of dental abscess according to anamnestic and diagnostic data and therapeutic management. A multiple logistic regression model was performed to evaluate the association of each variable with the healing time required for dental abscess. Results Variables associated with increased healing time were spring seasonality at admission, pyretic state, trismus, involvement of multiple anatomic spaces, and spontaneous drainage. Moreover, administration of some, but not all, classes of antibiotics was also associated with an increased healing time. Conclusions The knowledge of variables involved in healing time for dental abscess is crucial in the optimization of managing such infections in terms of cost–benefit ratio. This would represent a valuable way to ensure a shortened and more effective healing.